Antibiotic Resistance in Respiratory Tract Infections: Patterns, Mechanisms, and Intervention Strategies - Ahmad ganeed Ghorab; Ali Hamod Aseeri; Khaled Ahmed alshareef; Sami Abdullah AlGhamdi; Hameed Ataq almohalbdi; Hassan mohammed alharthi; Mohammed Majed Alsubaie; Khalil abdullah alqahtani; Tamim Mohammed alzahrani; Abdulrahman Mohammed alshareef; Ashraf marzouq alsulami; Ahmed Abdullah Asiri; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
1. Introduction Antibiotic resistance is an internationally recognized healthcare burden worsened by the increased consumption and improper use of antibiotics. Respiratory tract infections are the most common reason for the prescription of the majority of antibiotics in developed countries. Antibiotics have saved millions of lives since the discovery of penicillin in the early 20th century, but the increase in resistance is leading to a rise in the burden of both morbidity and mortality. Respiratory tract infections are associated with the most common antibiotic prescriptions in primary care, including the use of viral and antiviral therapies rather than antibiotics. In fact, less than 50% of the antibiotics prescribed in primary care are essential or appropriate. Viral respiratory tract infections are the most common cause of underused or inappropriate antibiotic prescriptions. This clearly illustrates the need for better biomarkers to guide the differences in diagnostic criteria used for viral and bacterial respiratory tract infections. Overuse has been associated with unnecessary patient risks, drug side effects, increased medical costs, and, as previously described, an increase in antibiotic resistance. As a matter of fact, antimicrobial resistance has its roots in the evolutionary response of microorganisms to antibiotics and is accelerated by the overuse and misuse of these drugs. Inappropriate administration is promoted by the incorrect selection, dosage, or duration of therapy, the misuse of broad-spectrum agents, or poor prevention measures in healthcare. Methods A systematic search was conducted in MEDLINE, the Cochrane Central Register of Controlled Trials, and EMBASE for guidelines on antimicrobial therapy up to October 2, 2016. Fifty-six guidelines yielded 546 antibiotic recommendations, primarily for penicillins (31%) and fluoroquinolones (22%). The most recommended antibiotics included amoxicillin (15%), cefazolin (14%), and ciprofloxacin (10%). Variability was observed in treatment durations, administration timings, dosages, and antibiotic selections among organizations. Recommendations for various syndromes should include facility-specific advice, especially for common infections like respiratory or gastrointestinal. Only three guidelines addressed organism-specific resistance patterns, while others lacked guidance. Surgical site infections are significant healthcare-related infections, emphasizing the need for risk-adjusted prophylaxis recommendations. Conclusion The assessment of resistance patterns from 28 studies in 47 countries found that Streptococcus pneumonia, Haemophilus influenzae, and Moraxella catarrhalis were commonly identified pathogens, with resistance rates to macrolides far exceeding those to penicillins in most countries (Elias et al., 2017). Azithromycin was the only macrolide tested, but it frequently had as much as 60% resistance or more in China, India, Poland, South Korea, and the United States. The highest resistance rate was reported for Mexico (97%). Resistance to macrolides in Europe and Canada was generally lower and not typically above 40%. In Europe and South Africa, the resistance rates of macrolides were slightly lower than those of S. pneumoniae. In China and the United States, H. influenzae had resistance rates similar to or higher than those of S. pneumoniae. As it was tested with azithromycin only, this could be due to differences between S. pneumoniae and H. influenzae, but the macrolide tested may have also contributed to the pattern of resistance rates. The studies in China and the United States also mostly tested lower RTI for H. influenzae infections. M. catarrhalis generally had lower resistance rates, particularly in later years. Nonetheless, above 40% rates were reported for this pathogen across seven studies in six countries.